Dementia and patient safety: A Gewirthian analysis. (June 2019) - Ó Néill, Clayton
This article deals with the relationship between dementia and patient safety and proposes that measures to promote patient safety should be situated within a rights-based framework. This article calls for the current perspectives on patient safety to be broadened to further encompass patient safety procedures that encompass a holistic and individualistic view of the patient. Alan Gewirth's Principle of Generic Consistency, as an underpinning moral principle, is applied in order to assess the appropriateness of current law, policy and practice. The article promotes the adoption of this principle as a moral justification for decisions that are taken in respect of patients with dementia and that are purported to protect their safety. It is argued that greater consideration needs to be given to ensuring that patient safety protocols are based upon a principled and empowering stance that does not impede the patient's realisation of self-fulfilment. This process will be facilitated by adopting rights-based patient safety measures that promotes empowerment. Through the narrative of a fictional patient, Molly, the article presents a novel way of conceptualising patients with dementia, involving the movement from presenting the patient in terms of a linear, declining progression towards a conceptualisation of the patient as a persisting self.